The Impact of Emotional Solidarity on Residents’ Attitude and Tourism Development - Hasani, Ali; Moghavvemi, Sedigheh; Hamzah, Amran (PLOS ONE, 2016)
In many countries, especially one such as Malaysia, tourism has become a key factor in economic development, and the industry heavily relies on feedback from local residents. It is essential to observe and examine the perceptions of residents towards tourists and tourism development for better planning in realizing successful and sustainable tourism development. Therefore, this research measured the relationship between residents’ welcoming nature, emotional closeness, and sympathetic understanding (emotional solidarity) towards tourists and their respective attitudes towards supporting tourism development. To test the proposed research model, we collected data using a questionnaire survey from 333 residents in rural areas in Malaysia. We used the structural equation modelling technique (Amos) to evaluate the research model, and the results revealed that the residents’ willingness (welcoming nature) to accept tourists is the strongest factor that effects the residents’ attitudes towards supporting tourism development. However, there was no significant relationship between residents’ emotional closeness and their sympathetic understanding towards tourists with their attitude and support towards tourism development. Welcoming nature, emotional closeness, and sympathetic understanding are able to predict 48% of residents’ attitudes towards tourism development and 62% of their support towards tourism development.